2017
DOI: 10.7554/elife.31661
|View full text |Cite
|
Sign up to set email alerts
|

Diverse functions of homologous actin isoforms are defined by their nucleotide, rather than their amino acid sequence

Abstract: β‐ and γ‐cytoplasmic actin are nearly indistinguishable in their amino acid sequence, but are encoded by different genes that play non‐redundant biological roles. The key determinants that drive their functional distinction are unknown. Here, we tested the hypothesis that β- and γ-actin functions are defined by their nucleotide, rather than their amino acid sequence, using targeted editing of the mouse genome. Although previous studies have shown that disruption of β-actin gene critically impacts cell migratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
80
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 37 publications
4
80
0
1
Order By: Relevance
“…While the cPM primarily consists of β-actin, the pPM is mostly built up from γ-actin. Understanding the non-redundant function of actin isoforms in cytoskeletal remodeling is an area of steeply emerging interest (46)(47)(48). Although not much is known about the different functions of the two isoforms, it is generally assumed that β-actin is preferentially located to protrusive lamellipodial structures and γ-actin to stress fibers (31), something which we also observed in DCs.…”
Section: Discussionsupporting
confidence: 59%
“…While the cPM primarily consists of β-actin, the pPM is mostly built up from γ-actin. Understanding the non-redundant function of actin isoforms in cytoskeletal remodeling is an area of steeply emerging interest (46)(47)(48). Although not much is known about the different functions of the two isoforms, it is generally assumed that β-actin is preferentially located to protrusive lamellipodial structures and γ-actin to stress fibers (31), something which we also observed in DCs.…”
Section: Discussionsupporting
confidence: 59%
“…We found the resulting mice, despite lacking β-actin protein, were born in Mendelian ratios and that the mice and derived fibroblasts appeared phenotypically normal. These results, together with those of a recent study using a similar approach (12) demonstrate that the nucleotide sequence is a critical determinant of actin isoformspecific function. However, we also found that β-actin protein is required to maintain the shape and function of auditory hair cells, demonstrating that other functions of cytoplasmic actins are defined by their amino acid sequences.…”
supporting
confidence: 75%
“…A recent study using clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 methodology also edited the endogenous Actb locus to express γ-actin protein (12), and the resulting mouse line is nearly identical to the one we independently generated and characterized here. Several of the same phenotypes were assessed, and very similar results were obtained.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Nevertheless, experiments with the purified isoforms show these can cause differences in polymerization rates (13), and cells have clearly been able to use these differentially to carry out different functions. Recently, Kashina and coworkers (14) demonstrated that the nucleotide sequence of the two genes may play a significant factor in differential actin utilization. Whereas elimination of beta actin is lethal, these authors found that editing the beta actin gene to produce gamma actin did not cause lethality.…”
mentioning
confidence: 99%